ANALISIS KETAHANAN KELUARGA DALAM PEMULIHAN ADIKSI NARKOTIKA MELALUI PENDEKATAN EKOLOGI KELUARGA - Martha Istyawan; Margaretha Hanita; Diah Setia Utami (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2023)
In undergoing the recovery process of drug addiction, participation from the family is needed, as in an ecological perspective, the family is the relationship between individuals in the family, family relations with the social environment, and relations between the social environment and all its ecosystems. The study aims to analyze family resilience in the recovery of drug addiction through a family ecology approach (micro, meso, and macro). This research is qualitative and descriptive with a literature review method. As a result, the correlation between micro, meso, and macro aspects can help maximize family resilience in supporting the recovery process from drug addiction. Conversely, if these three aspects are constrained, they will impact the recovery process of drug addiction.   The synergy of the three ecological aspects is expected to support family resilience in the recovery process of drug addiction to reduce the recurrence rate (relapse) of drug abuse in Indonesia.